TRAIL and its receptors in cardiac diseases - Grisanti, Laurel A. (Frontiers in Physiology, 2023)
Cardiovascular disease is a leading cause of death worldwide. Loss of cardiomyocytes that occurs during many types of damage to the heart such as ischemic injury and stress caused by pressure overload, diminishes cardiac function due to their limited regenerative capacity and promotes remodeling, which further damages the heart. Cardiomyocyte death occurs through two primary mechanisms, necrosis and apoptosis. Apoptosis is a highly regulated form of cell death that can occur through intrinsic (mitochondrial) or extrinsic (receptor mediated) pathways. Extrinsic apoptosis occurs through a subset of Tumor Necrosis Receptor (TNF) family receptors termed "Death Receptors." While some ligands for death receptors have been extensively studied in the heart, such as TNF-α, others have been virtually unstudied. One poorly characterized cardiac TNF related ligand is TNF-Related Apoptosis Inducing Ligand (TRAIL). TRAIL binds to two apoptosisinducing receptors, Death Receptor (DR) 4 and DR5. There are also three decoy TRAIL receptors, Decoy Receptor (DcR) 1, DcR2 and osteoprotegerin (OPG). While TRAIL has been extensively studied in the cancer field due to its ability to selectively induce apoptosis in transformed cell types, emerging clinical evidence points towards a role for TRAIL and its receptors in cardiac pathology.